Yahoo Web Search

  1. Sort by

  1. ...1/2^n) = -63 Hence 2 + 1 + ... + 1/2^n = 63/16 The sum on the LHS is 2(1 - 1/2^n) / (1/2) = 4(1 - 1/2^n) and the RHS is 4...

    1 Answers · Science & Mathematics · 07/07/2017

  2. ... P(n)=3+9+27+...+3^n=3(3^n-1)/2 be a proposition. (1) n=1=>LHS=3 & RHS=3(3^1-1)/2=3=LHS=>P(1) is true. (2...

    3 Answers · Science & Mathematics · 16/06/2017

  3. ...identity; sin(x) =/= 0 (x =/= n * pi in radians if n is an integer) on the LHS, while the RHS doesn't have that restriction.

    4 Answers · Science & Mathematics · 26/07/2017

  4. ... sin(theta) =/= 0, so theta cannot be 0 and every pi after that ; on the LHS cos(theta) =/= 0, 1, or -1, so theta cannot be 0 and every pi/2 after that...

    4 Answers · Science & Mathematics · 04/06/2017

  5. ...by looking at the equation that x ≠ - 1 and x ≠ 0. Simplify the LHS to obtain : (using the laws of logs! ) log (x + 1) - logx = log2...

    6 Answers · Science & Mathematics · 03/06/2017

  6. ...say? [(9^{2x - 1})(3^{3x})^2]/(27^{x + 2})^3 = 81^3. Well, the numerator of the LHS reduces to (9^{2x - 1})(3^{3x})^2 = (9^{2x - 1})(3^{6x}) = (3^{4x - 2})(3^{6x...

    1 Answers · Science & Mathematics · 25/05/2017

  7. ...2 x = 1 for all values of x, i.e., an identity LHS = cos^2 x / sin^2 x - sin^2 x / cos^2 x = (cos^4...should be 2 . 13: 2 tan x / (1-tan^2 x) = 1 The LHS is the double angle formula for tan (2x); so tan (2x...

    3 Answers · Science & Mathematics · 13/05/2017

  8. ∫ [(2+2y^2)dy]/y = ∫ e^x dx RHS = e^x + C LHS just divide each term by y ∫ (2/y+2y^2/y) dy ∫ 2dy/y + ∫ 2y dy 2 ln|y| + ...

    3 Answers · Science & Mathematics · 11/05/2017

  9. What do you get when you evaluate the LHS? Since v = 11.4 km/s is suspiciously close to the escape velocity, you should...

    1 Answers · Science & Mathematics · 01/05/2017

  10. to prove cotA - cot2A = csc2A work on the LHS cosA/sinA - cos2A/sin2A use identities...

    3 Answers · Science & Mathematics · 02/05/2017

  1. Try asking your question on Yahoo Answers